An Estimation of Parameters For Exponentiated Burr Type XII Distribution Based on Ranked Set Sampling: parameter Estimation for EBXII and Fisher information matrix based on RSS - Abdallah Abdelfattah; Nagwan Reyad Elshendidy (JOURNAL OF ADVANCES IN MATHEMATICS, 2020)
The aim of this paper is to estimate the parameters of exponentiated Burr type XII distribution (EBXII) based on ranked set sampling (RSS) technique, and also simple random sampling(SRS) is provided by the method of maximum likelihood. Fisher information matrix for both (SRS) and (RSS) for the unknown parameters are derived. Simulation study compared between the estimators of both methods in terms of their biases, mean square errors, and efficiencies. It is shown that the estimators based on RSS are more efficient than those of SRS.